LCA methodology applied to the realisation of a domestic plate: confrontation among the use of three different raw materials. (2016) - Postacchini, Leonardo; Bevilacqua, Maurizio; Paciarotti, Claudia; Mazzuto, Giovanni
This paper aims at assessing the environmental impact of a household product such as a domestic plate, comparing, through the use of the life cycle assessment (LCA) methodology, three different materials in which it can be made: plastic (polypropylene), ceramics and mater-bi (biodegradable plastic). To better understand all stages of the life cycle of each type of plate, the study has been divided into three parts: manufacture, use and disposal. These three phases join in a single project for each type of plate, in order to compare the environmental final impacts of the three life cycles. This study focuses on the comparison of the environmental impacts of the different types of plate, analysing the results of the LCA, their accuracy, and, at the same time, identifying the critical stages. In this study the LCA software SimaPro 7.3.3 has been used.